2014
DOI: 10.1039/c3ra46736h
|View full text |Cite
|
Sign up to set email alerts
|

A dual-ionic liquid microemulsion system for the selective isolation of hemoglobin

Abstract: A novel dual-ionic liquid (IL) microemulsion system is developed with IL 1-decyl-3-methylimidazolium bromide (DmimBr) as the surfactant and IL 1-butyl-3-methylimidazolium hexaflourophosphate (BmimPF 6 ) as a substitute for organic solvent. The phase diagram of this dual-IL microemulsion system clearly shows the formation of a single phase within a wide range of BmimPF 6 (1.76-98.3%, wt) and in the presence of an appropriate amount of DmimBr and water. The microemulsion is characterized by means of FT-IR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…S7(A)) are almost the same as that obtained for native Hb (1657 and 1542cm −1 , Fig. S7(B)), and are essentially consistent with the reported value of native Hb (Ma and Tian, 2010;Mao et al, 2014;Sun et al, 2013;Sun et al, 2009). The similarities of the two spectra demonstrated that Hb retained the essential features of its native secondary structure on Nafion/Hb/TiO 2 -Ti 3 C 2 composite film.…”
Section: Spectroscopic Characterization Of Nafion/hb/tio 2 -Ti 3 C 2 supporting
confidence: 92%
See 1 more Smart Citation
“…S7(A)) are almost the same as that obtained for native Hb (1657 and 1542cm −1 , Fig. S7(B)), and are essentially consistent with the reported value of native Hb (Ma and Tian, 2010;Mao et al, 2014;Sun et al, 2013;Sun et al, 2009). The similarities of the two spectra demonstrated that Hb retained the essential features of its native secondary structure on Nafion/Hb/TiO 2 -Ti 3 C 2 composite film.…”
Section: Spectroscopic Characterization Of Nafion/hb/tio 2 -Ti 3 C 2 supporting
confidence: 92%
“…This reveals that TiO 2 -Ti 3 C 2 nanocomposite has biocompatibility and did not suffer significant protein denaturation. FTIR spectroscopy is also an effective means to explore the secondary structure of Hb entrapped in Nafion/Hb/TiO 2 -Ti 3 C 2 composite film (storage at 4 °C for 60 days) (Liu et al, 2015a;Lu et al, 2008;Mao et al, 2014;Sun et al, 2014a). The shapes of amide I and amide II bands of protein provide detailed information on the secondary structure of polypeptide chain (Kauppinen et al, 1981).…”
Section: Spectroscopic Characterization Of Nafion/hb/tio 2 -Ti 3 C 2 mentioning
confidence: 99%
“…The IL [C 10 C 1 im]Br was used as the surfactant and the IL [C 4 C 1 im][PF 6 ] as substitute for the organic solvent. 277 The dual-IL microemulsion system proved to be more effective for the extraction of proteins in comparison with the isolated [C 4 C 1 im][PF 6 ] system. Lower pH values were found to be favorable for the selective extraction of Hb, as a result of the coordination interaction between the heme group of Hb and the imidazolium cationic moiety, 277 and in agreement with the results of Shu et al 276 By adding an alkaline Britton–Robinson buffer at pH 12, the authors also performed the back-extraction of the protein with a recovery yield of 55.6%.…”
Section: Proteinsmentioning
confidence: 99%
“… 277 The dual-IL microemulsion system proved to be more effective for the extraction of proteins in comparison with the isolated [C 4 C 1 im][PF 6 ] system. Lower pH values were found to be favorable for the selective extraction of Hb, as a result of the coordination interaction between the heme group of Hb and the imidazolium cationic moiety, 277 and in agreement with the results of Shu et al 276 By adding an alkaline Britton–Robinson buffer at pH 12, the authors also performed the back-extraction of the protein with a recovery yield of 55.6%. 277 In summary, and although only briefly investigated, both works 273 , 274 demonstrated the potential applicability of IL-based microemulsions for the isolation of Hb from human whole blood samples, while opening the path to explore this type of system for the purification of other proteins from real and complex matrices.…”
Section: Proteinsmentioning
confidence: 99%
“…One of the ways to increase the extraction efficiency is to increase the contact area between the ionic liquid and a solution containing ions that need to be extracted. This can be accomplished by creating a nano-emulsion of the ionic liquid, which greatly increases its surface area, minimising the amount of material required for extraction [9][10][11]. Moreover, nano-emulsions are kinetically stable, and their small size makes them resistant to sedimentation or creaming [12], providing greater control over the extraction process, and allowing for greater storage times.…”
Section: Introductionmentioning
confidence: 99%